Mali : Poverty Reduction Strategy Paper Implementation Report. (IMF Staff Country Reports; Country Report, 2006)
This paper discusses the Poverty Reduction Strategy Paper Implementation Report 2003-04 for Mali. Progress has been made in the social sectors, even if some inadequacies remain. Budget allocations to the education and health sectors have improved, with budget resources allotted to essential social services trending markedly favorably over the period 2001-04. The program to restructure and privatize public enterprises is well advanced. Railroads have been private since 2003, and a privatization support unit was established for the Malian Telecommunications Company SOTELMA.